In silico Methods for Design of Kinase Inhibitors as Anticancer Drugs - Gagic, Zarko; Ruzic, Dusan; Djokovic, Nemanja; Djikic, Teodora; Nikolic, Katarina (Frontiers in Chemistry, 2020)
Rational drug design implies usage of molecular modeling techniques such as pharmacophore modeling, molecular dynamics, virtual screening and molecular docking, to explain activity of biomolecules, define molecular determinants for interaction with the drug target and design more efficient drug candidates. Kinases play essential role in cell function and therefore are extensively studied targets in drug design and discovery. Kinase inhibitors are clinically very important and widely used antineoplastic drugs. In this review, computational methods used in rational drug design of kinase inhibitors are discussed and compared, considering some representative case studies.